2010
DOI: 10.1016/j.virusres.2010.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the BK virus subtypes and their influence on viral in vitro growth efficiency

Abstract: SUMMARYThe major capsid protein, VP1, of the human Polyomavirus BK (BKV) is structurally divided into five outer loops, referred to as BC, DE, EF, GH, and HI. The BC loop includes a short region, named the BKV subtyping region, spanning nucleotides 1744-1812 and characterized by non-synonymous nucleotide polymorphisms that have been used to classify different strains of BKV into four subtypes. The aim of this study was to determine if the nucleotide changes clustered within the BKV subtyping region may influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Polyomavirus of the family Polyomaviridae which also includes JCV, SV40 and the newly discovered WI, KU, and MC viruses [Tremolada et al, 2010]. BKV infection is generally acquired in childhood and is usually asymptomatic.…”
Section: Bk Polyomavirus (Bkv) Is a Member Of The Genusmentioning
confidence: 99%
“…Polyomavirus of the family Polyomaviridae which also includes JCV, SV40 and the newly discovered WI, KU, and MC viruses [Tremolada et al, 2010]. BKV infection is generally acquired in childhood and is usually asymptomatic.…”
Section: Bk Polyomavirus (Bkv) Is a Member Of The Genusmentioning
confidence: 99%
“…Indeed, cell culture studies have underscored the importance of the VP1 composition for propagation of BKV. In human renal epithelial cells, subtype I strains grew more efficiently than subtype IV strains (Nukuzuma et al, 2006), while in Vero cells, subtype III displayed lower replication capacity than the other subtypes (Tremolada et al, 2010c). A study of Vero cells infected with BKV mutants containing substitutions in several charged amino acids within VP1 loops BC, DE, and HI showed that some of these mutants were deficient in genome packaging, capsid assembly, or binding to host cells (Dugan et al, 2007).…”
mentioning
confidence: 99%
“…Subtypes II and III are rarely identified, though primer and/or probe subtype-specific mismatches in certain BKV molecular diagnostic assays may contribute to underdetection (1,10). Interestingly, BKV subtype III demonstrates reduced replicative capacity in vitro (11). This may correspond to limited pathogenicity in vivo and contribute to the low prevalence of BKV subtype III worldwide.…”
mentioning
confidence: 99%
“…We identified viral amino acid changes that are unique among BKV sequences, most of which affected the BC loop of VP1. It has been proposed that amino acid changes within the BC loop may be associated with an increase in pathogenic potential and therefore may contribute to the development of BKVN (11,12). In addition, phosphorylation has been hypothesized to influence VP1 function, and two of the amino acid changes (P59S and N61T) create potential new phosphorylation sites for cellular kinases (13).…”
mentioning
confidence: 99%